Use of Flavin-Related Cellular Autofluorescence to Monitor Processes in Microbial Biotechnology - Müllerová, Lucie; Marková, Kateřina; Obruča, Stanislav; Mravec, Filip (Microorganisms, 2022)
Cellular autofluorescence is usually considered to be a negative phenomenon because it can affect the sensitivity of fluorescence microscopic or flow cytometric assays by interfering with the signal of various fluorescent probes. Nevertheless, in our work, we adopted a different approach, and green autofluorescence induced by flavins was used as a tool to monitor fermentation employing the bacterium Cupriavidus necator. The autofluorescence was used to distinguish microbial cells from abiotic particles in flow cytometry assays, and it was also used for the determination of viability or metabolic characteristics of the microbial cells. The analyses using two complementary techniques, namely fluorescence microscopy and flow cytometry, are simple and do not require labor sample preparation. Flavins and their autofluorescence can also be used in a combination with other fluorophores when the need for multi-parametrical analyses arises, but it is wise to use dyes that do not emit a green light in order to not interfere with flavins' emission band (500-550 nm).
Keywords: flavins; bacteria; viability; green autofluorescence; average fluorescence lifetimes